The juvenile hormone described in Rhodnius prolixus by Wigglesworth is juvenile hormone III skipped bisepoxide - Villalobos Sambucaro, María José (2020)
Juvenile hormones (JHs) are sesquiterpenoids synthesized by the corpora allata (CA). They play critical roles during insect development and reproduction. The frst JH was described in 1934 as a “metamorphosis inhibitory hormone” in Rhodnius prolixus by Sir Vincent B. Wigglesworth. Remarkably, in spite of the importance of R. prolixus as vectors of Chagas disease and model organisms in insect physiology, the original JH that Wigglesworth described for the kissing-bug R. prolixus remained unidentifed. We employed liquid chromatography mass spectrometry to search for the JH homologs present in the hemolymph of fourth instar nymphs of R. prolixus. Wigglesworth’s original JH is the JH III skipped bisepoxide (JHSB3), a homolog identifed in other heteropteran species. Changes in the titer of JHSB3 were studied during the 10-day long molting cycle of 4th instar nymph, between a blood meal and the ecdysis to 5th instar. In addition we measured the changes of mRNA levels in the CA for the 13 enzymes of the JH biosynthetic pathway during the molting cycle of 4th instar. Almost 90 years after the frst descriptions of the role of JH in insects, this study fnally reveals that the specifc JH homolog responsible for Wigglesworth’s original observations is JHSB3.